Reforming mode of cadres selection in Vietnam today - Dr. Nguyen Minh Tuan, (The journal of contemporary issues in business and government, 2021)
Experience of the world shows that building a team of leaders and managers is always the top priority in the human resource development strategy. For Vietnam, in order to well develop human resources - one of the three breakthroughs in socio- economic development and reform of the civil service regime, civil servants, the quality improvement of the contingent of cadres, leadership, management is always an urgent requirement and is a requirement of current practice. Leadership and management team is built through many solutions such as discovering, recommending, recommending, attracting, retraining, planning, dismissing, etc. In which, how to choose Choosing someone worthy of appointment is a decisive content to the quality of the leadership and management team. This study focuses on analyzing the model of the political system’s cadres selection; the problems posed and the causes of inadequacies in the mode of staff selection in the current political system in Vietnam; from there, proposing solutions for innovating the mode of selecting cadres in the political system in Vietnam in the coming time.